LEGAL FRAMEWORK FOR THE POST-PANDEMIC TOURISM IN BALI - Stefan Koos (Warmadewa Press, 2021)
Tourism can only thrive when customers feel welcome. Especially in the time of the restart of the tourism industry after the pandemic, there may be an opportunity for the Indonesian tourism industry to correct undesirable developments in the past in order to promote a type of tourism that is sustainable, honest and effective. This concerns economic and strategic marketing decisions, such as addressing specific target groups for tourism services, but also legal framework conditions. Corresponding legal framework conditions can be found particularly in consumer protection law and competition law, but also in the hierarchy between Indonesian federal law and local law. From the point of view of a foreign observer, the paper would like to highlight some legal aspects that could be important for a rebalancing of tourism.